Paleoenvironment of Jawa basalt plateau, Jordan, inferred from calcite speleothems from a lava tube - Frumkin, A; Bar-Matthews, M; Vaks, A (2008)
This paper explores the environmental conditions that faced the people of ancient Jawa during the Holocene, as well as previous prehistoric periods of the mid-late Pleistocene. Calcite speleothems in a lava tube are dated using the U-Th method, to marine oxygen isotope stage 7 from ∼ 250 to 240 ka and from ∼ 230 to ∼ 220 ka; and the stage 5/4 transition between ∼ 80 and 70 ka. The available evidence indicates general aridity of the Black Desert during most of the mid-late Quaternary, punctuated by short wetter periods, when the Mediterranean cyclonic systems intensified and penetrated the north Arabian Desert. These Mediterranean systems had a longer and more intense effect on the desert fringe closer to the Mediterranean and only rarely penetrated the Black Desert of Jawa. The results do not exclude some increase of rainfall which did not change water availability dramatically during the warm Holocene. The ancient Jawa city appears to have depended on technological ability to build elaborate runoff-collection systems, which became the prime condition for success. © 2008 University of Washington.